Download presentation
Presentation is loading. Please wait.
Published byAustin Lee Modified over 5 years ago
2
2x + 5y = x + 3y = 22 How can we solve this equation by elimination?
4
You Try…Solve by elimination
–2x + 15y = –32 7x – 5y = 17 3(7x – 5y = 17) 21x – 15y = 51 –2x + 15y = –32 21x – 15y = 51 19x = x = 1 7x – 5y = 17 7(1) – 5y = 17 7 –5y = 17 –5y = 10 –5 –5 y = –2 (1, –2)
8
15x + 3y = 9 10x + 7y = -4 7(15x + 3y = 9) 3(10x + 7y = –4) 105x + 21y = 63 30x + 21y = x – 21y = 12 75x = x = 1 15x + 3y = 9 15(1) + 3y = y = y = y = -2 (1,-2)
9
Homework
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.